Comparing the Islamic Rural Banks (BPRS) Soundness on Java Area Before and During the Pandemic - Sari, Henny Rahma; Canggih, Clarashinta (MALIA: Journal of Islamic Banking and Finance, 2021)
Thestudy aimed to compare the Islamic Rural Banks (BPRS) soundness on Java area before and during the pandemic. The research is a quantitative study using secondary data obtained from the monthly Islamic Banking statistics published by Otoritas Jasa Keuangan. The sample was DPK, NPF, and FDR of BPRS in 6 provinces at Java island from May 2019 until November 2020. The analysis of the data in this study used Wilcoxon analysis. The results of the study indicated there is a different of BPRS soundness, represented by DPK, NPF, and FDR before and during the pandemic covid-19.